2020
DOI: 10.1007/s00414-020-02387-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of phase II metabolism of 11-hydroxy-Δ-9-tetrahydrocannabinol and metabolite verification by chemical synthesis of 11-hydroxy-Δ-9-tetrahydrocannabinol-glucuronide

Abstract: (−)-Δ-9-tetrahydrocannabinol ((−)-Δ-9-THC) is the main psychoactive constituent in cannabis. During phase I metabolism, it is metabolized to (−)-11-hydroxy-Δ-9-tetrahydrocannabinol ((−)-11-OH-Δ-9-THC), which is psychoactive, and to (−)-11-nor-9-carboxy-Δ-9-tetrahydrocannabinol ((−)-Δ-9-THC-COOH), which is psychoinactive. It is glucuronidated during phase II metabolism. The biotransformation of (−)-Δ-9-tetrahydrocannabinol-glucuronide ((−)-Δ-9-THC-Glc) and (−)-11-nor-9-carboxy-Δ-9-tetrahydrocannabinol-glucuroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Drawing parallels with the human metabolism of THC and CBD, it was anticipated that metabolic transformation reactions would involve Position 11 as well as the pentyl side chain ( 6–8 ). Additionally, it was expected that both the parent drug and its oxidized forms might undergo glucuronidation reactions ( 9 ). Leveraging the available LC–MS-MS data, these hypotheses were verified, enabling insights into the biotransformation pathways of HHC in humans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing parallels with the human metabolism of THC and CBD, it was anticipated that metabolic transformation reactions would involve Position 11 as well as the pentyl side chain ( 6–8 ). Additionally, it was expected that both the parent drug and its oxidized forms might undergo glucuronidation reactions ( 9 ). Leveraging the available LC–MS-MS data, these hypotheses were verified, enabling insights into the biotransformation pathways of HHC in humans.…”
Section: Resultsmentioning
confidence: 99%
“…Another observed metabolism route for CBD includes oxidation of the pentyl side chain ( 7 , 8 ). Phase II metabolism primarily involves glucuronidation, with parent drugs and their oxidized forms as precursors ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The wide availability of cannabis necessitates warning against its misuse (Carvalho and Evans-Gilbert, 2019) as there have been numerous case reports of acute cannabis intoxication resulting in seizures, ataxia, lethargy, tremors, and even comas among children (Emoto and Kallail, 2020). Cannabis or THC is becoming increasingly important as a therapeutic agent (Hassenberg et al, 2020). Although THC is considered the principal psychoactive agent of the cannabis plant (Dumbraveanu et al, 2023), and 11-OH-THC is the primary metabolite of THC, there is limited data on the pharmacology of 11-OH-THC.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the association of UGT1A9 polymorphism with the metabolism of cannabinoids are limited. A recent study demonstrated significantly lower 11-OH-THC concentrations of homozygote carriers of the derived alleles in UGT1A9 440/331 compared with homozygote carriers of the ancestral alleles [ 244 , 245 ].…”
Section: Pharmacogenomics Of Metabolismmentioning
confidence: 99%